Aktivitas Antikolesterol Kombinasi Ekstrak Eksokarp Buah Semangka (Citrullus Lanatus (Thunb.) dan Ekstrak Daun Salam (Syzygium Polyanthum) pada Mencit Jantan Galur balb/c: ANTICHOLESTEROL ACTIVITY OF WATERMELON EXOCARP EXTRACT (Citrullus Lanatus (Thunb.)) AND BAY LEAF EXTRACT (Syzygium Polyanthum) IN MALE MICE OF balb/c STRAIN - Kusuma, Ikhwan Yuda; Noryana; Octaviani, Peppy (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Watermelon fruit exocarp (Citrullus lanatus Thunb.) and bay leaf (Syzygium polyanthum) are both known to contain flavonoid compounds with anticholesterol properties. This study aims to determine the comparison of the effects of watermelon fruit exocarp extract with bay leaf extract in single, and the combination of both in reducing cholesterol levels. Hypercholesterolemia induction was done by giving propylthiouracil (PTU) suspension. This research method was conducted experimentally with a pre-test and post-test design with a control group. Mice were divided into 6 groups, i.e., experimental groups (1, 2, and 3) with negative control (K-), positive control (K+), and normal control (KN). The doses used were (K1) watermelon fruit exocarp extract 500 mg/kg, (K2) bay leaf extract 400 mg/kg, and (K3) combination of watermelon fruit exocarp extract and bay leaf extract 500: 400 mg/kg, all treatment was given for 14 days. The (K-) group was given 1% Na-CMC, K+ was given Simvastatin 10 mg/kgBB, and (KN) without treatment. The results of this study showed a reduction in total cholesterol levels in mice in the K+, K-, and KN groups, i.e., 50.67±35.82mg/dL, 2.67±1.89mg/dL, and 6.66±4.70mg/dL, respectively. While in the K1, K2, and K3 test groups, cholesterol levels decreased, i.e., 51±36.06 mg/dL, 50.33±35.59 mg/dL, and 86.67±61.28mg/dL, respectively. Regarding to our result, the three groups showed an effect in lowering the total cholesterol level in mice with the average cholesterol level in the pre-test and post-test. The highest decrease showed on the combination group compared to the single group.